THEUSE OF INULIN-CONTAINING PLANTS AS A SOURCE OF BIOLOGICALLY ACTIVE COMPOUNDS OF ANTIOXIDANT ACTIVITY - ValeriaNikolaevna Orobinskaya (Современная наука и инновации, 2022)
The article discusses the questions of localization offructans in food plants, the market offructans production, the technology of producing fructans and inulin, as well as the opportunity of using of inulin as a biologically active compound of antioxidant action.